Investigating the Potential of Extracellular Vesicles as Delivery Systems for Chemotherapeutics - Alessia Brancolini; Riccardo Vago (Biomedicines, 2024)
Background/Objectives: Standard chemotherapy is generally considered the best approach to treat many solid cancers, even accounting for severe side effects. Therefore, the development of a drug delivery system for chemotherapeutic administration could significantly improve standard chemotherapy by maintaining the cytotoxic effects of the drugs while decreasing the inherent side effects of the treatment. The aim of our study is the optimization of a loading strategy that conjugates the use of extracellular vesicles (EVs) as drug delivery carriers, by preserving their integrity, with the loading efficiency and activity maintenance of chemotherapeutics. Methods: We compared the EV loading of the chemotherapeutics epirubicin, mitomycin, methotrexate and mitoxantrone by co-incubation. Once loaded, the activity of drug-carrying EVs was tested on cancer cells and compared to that of free chemotherapeutics. Results: We defined a linear correlation between chemotherapeutics’ concentration and their absorbance at the drug-specific wavelength, which allowed the definition of a highly sensitive absorbance-based spectrophotometric quantification system, enabling the assessment of drug loading efficiency. Co-incubation of EVs and chemotherapeutics was sufficient to obtain quantifiable drug loading, and the efficacy of EV loading was drug-dependent. Epirubicin-loaded vesicles showed increased toxicity to bladder cancer cells with respect to the free chemotherapeutic. The cytotoxicity was maintained even upon 6-month storage at −80 °C of loaded EVs. Conclusion: We established an absorbance-based spectrophotometric quantification system that enables a straightforward measure of drug loading efficiency into EVs, and we demonstrated that chemotherapeutic-carrying EVs can be obtained by co-incubation, preserving and increasing drug cytotoxicity.